QUO VADIS VILLAGE FINANCIAL MANAGEMENT: TRANSPARENCY VS ACCOUNTABILITY (CASE STUDY IN BOGOR DISTRICT) - Rochman Marota; Agung Fajar Ilmiyono; Indah Setiarini Erganda (School of Business, Bogor Agricultural University (SB-IPB), 2021)
Villages obtain their sources of income from original village income, transfers, and other income. Considerable income makes the village government demand to increase transparency and accountability along with the development of public sector accounting. However, transparency and accountability are still a problem for some villages. This study aimed to determine the effect of transparency and accountability on the financial management in 13 villages in Sukaraja District, Bogor Regency. The data were collected using a questionnaire distributed to 83 respondents, selected using the purposive sampling method. The data analysis methods included a validity test, reliability test, t-test, f-test, coefficient of determination test, multiple linear regression, normality test, heteroscedasticity test, and descriptive statistics. Partial testing with t-test showed that transparency had no significant effect on village financial management because some respondents answered that they disagreed. Therefore, it can be concluded that transparency had been implemented but not yet maximized. While accountability partially had a significant effect on village financial management, accountability had run well. Based on the simultaneous testing results with the f-test, transparency and accountability simultaneously positively affected village financial management. Keywords: village financial management, village government, transparency, accountability, multiple linear regression